Programmed Degradation of Pericarp Cells in Wheat Grains Depends on Autophagy - Li, Yong-Bo; Yan, Mei; Cui, De-Zhou; Huang, Chen; Sui, Xin-Xia; Guo, Feng Zhi; Fan, Qing-Qi; Chu, Xiu-Sheng (Frontiers in Genetics, 2021)
Wheat is one of the most important food crops in the world, with development of the grains directly determining yield and quality. Understanding grain development and the underlying regulatory mechanisms is therefore essential in programs aimed at improvement. In this study, the developmental characteristics of the pericarp was examined in developing wheat grains of the new variety Jimai 70. As a result, pericarp thickness was found to be thinnest in grains at the top of the spike, followed by those in the middle and thickest at the bottom. Moreover, this difference corresponded to the number of cell layers in the pericarp, which decreased as a result of programmed cell death (PCD). A number of autophagy-related genes (ATGs) are involved in the process of PCD in the pericarp, and in this study, an increase in ATG8-PE expression was observed followed by the appearance of autophagy spots. Meanwhile, following interference of the key autophagy gene ATG8, PCD was inhibited and the thickness of the pericarp increased, resulting in small premature grains. These findings suggest that autophagy and PCD coexist in the pericarp during early development of wheat grains, with both processes increasing from the bottom to the top of the spike. Moreover, PCD was also found to rely on ATG8-mediated autophagy. The results of this study therefore provide a theoretical basis for in-depth studies of the regulatory mechanisms of wheat grain development.